ANALISIS VARIABEL YANG MEMPENGARUHI EARNING PER SHARE DAN HUBUNGANNYA TERHADAP PRICE TO BOOK VALUE - Yulianingsih, Sovia (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: One of the information that commonly used by investors in evaluating bank shares is the ratio of Price to Book Value (PBV). In addition to PBV, the ratio of Earning Per Share (EPS) is also considered as another important factor. This study examines the factors that affect EPS and PBV. These include Return on Equity (ROE), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), and Operational Cost and Operational Income (BOPO). A total of 26 banks in Indonesia is used as the sample from2009 to 2011. Data were analyzed using Path Analysis. The results show that NPL affects EPS, while EPS and BOPO affect PBV. Keywords: ROE, CAR NPL, NIM, BOPO, EPS, PBV.